Micro quantification of human placenta in chronic hypoxia - Chabes y Suárez, Álvaro (2015)
We carried out a quantitative study of 50 placentas micro tall (Juliaca, Peru 3,840 m) and 50 placentas from Lima, 150 m (Maternity hospital).